Introduction to emergency management George D. Haddow, Jane A. Bullock, Damon P. Coppola - Haddow, George D.; Bullock, Jane A.; Coppola, Damon P. (Butterworth-Heinemann is an imprint of Elsevier, 2021)
Introduction to Emergency Management, Seventh Edition, sets the standard for excellence in the field and has educated a generation of emergency managers. This long-trusted resource provides a broad overview of the key aspects of the emergency management profession. Readers will gain an understanding of why the emergency management profession exists, what actions its professionals and practitioners are tasked with performing, and what achievements are sought through the conduct of these various efforts. Students and new professionals alike will further gain an enhanced understanding of key terminology and concepts that enable them to work with emergency management specialists.